2016
DOI: 10.1021/acs.jnatprod.6b00027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Birch Bark Triterpenes on Keratinocytes and Fibroblasts from Diabetic and Nondiabetic Donors

Abstract: Impaired wound healing is one of the main risk factors associated with diabetes mellitus. Few options are available to treat diabetic wounds, and therefore efficient remedies are urgently needed. An interesting option might be an extract of birch bark (TE) that has been clinically proven to accelerate acute wound healing. We investigated the effects of TE and its main components betulin and lupeol in cultured normal keratinocytes and dermal fibroblasts from diabetic and nondiabetic donors. These in vitro model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 63 publications
0
16
0
1
Order By: Relevance
“…As the major second type of cells in the skin is fibroblasts, we tested whether TE might induce the expression of cytokines in fibroblasts under different glucose conditions. We investigated cytokines which have previously been shown to be induced by TE in fibroblasts under normal culture conditions [30] and which are important for wound healing[31]. We observed a significant increase of IL-6, IL-8, IL-1 ß, and CCL-2 expression in fibroblasts under various glucose concentrations (Table 2).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As the major second type of cells in the skin is fibroblasts, we tested whether TE might induce the expression of cytokines in fibroblasts under different glucose conditions. We investigated cytokines which have previously been shown to be induced by TE in fibroblasts under normal culture conditions [30] and which are important for wound healing[31]. We observed a significant increase of IL-6, IL-8, IL-1 ß, and CCL-2 expression in fibroblasts under various glucose concentrations (Table 2).…”
Section: Resultsmentioning
confidence: 90%
“…As we knew about the beneficial effect of TE in-vivo and ex-vivo under euglycaemic conditions [2224] and its effect on cytokine production and cytoskeleton in diabetic keratinocytes and fibroblasts [30] and because triterpenes are known to have beneficial effects in diabetes[40], we used TE as a test substance in our various in-vitro and ex-vivo models. Interestingly, it only showed a positive effect in the ex-vivo model.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that IL‐8 was increased in diabetic wounds and that baseline levels of the IL‐8 mRNA were elevated in human dermal fibroblasts from diabetic donors compared with that from nondiabetic donors . Thus, determine whether IL‐8 was highly expressed in diabetic wound exudates, four exudate samples were collected with DFUs, and the amount of IL‐8 was quantified by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Base on the effects of IL‐8 in the chemotaxis of neutrophils and the recruitment of neutrophils on the upregulation and overexpression of several α defensins, we hypothesized that α defensins may be involved in IL‐8 production. As resident cells of the skin, fibroblasts are essential for wound healing; however, the roles of fibroblasts in pathological functions in diabetic wounds remain largely unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation